EFFECT OF LO'I KARANA ON PAIN LEVEL IN POSTPARTUM MOTHERS - Rini Hendari; Dahlan H Ahmad; A Haris (Belitung Raya Foundation, Indonesia, 2018)
Background: Lo'i karana is one type of traditional therapies that has existed for more than one hundred years in the midst of society of Bima and Dompu to overcome the discomfort due to labor. However, lack of research has been conducted to examine its effect on pain in postpartum mothers. Objective: To examine the effect of Lo’i karana on muscle pain in postpartum mothers. Methods: This was a quasi-experimental study with posttest only control group design. Thirty mothers were selected using purposive sampling, which 10 assigned in 3 groups (standard-dose group, minimal-dose group, and maximal-dose group). Wong-Baker Faces Pain rating scale was used to measure pain on day 1 and day 3. Kruskal-Wallis Test and Mann Whitney test were used for data analysis. Results: There were significant effects of Lo’i karana in minimal, standard and maximal dosage on pain level in the first day (p=0.004) and the third day (p=0.009) in postpartum mothers. The results revealed that the higher doses were used for the treatment, the less pain of the mothers would be. Conclusion: Lo’i karana has a significant effect in reducing pain level in postpartum mothers. It is recommended that this intervention can be applied as a part of nursing intervention in caring postpartum mothers.